The need for technical education - with special reference to Saorstat Eireann - Clampett, G.J.T. (Statistical and Social Inquiry Society of Ireland, 1929)
Technical Education should offer to all citizens, especially to the young citizens, facilities to obtain instruction in the theory, and to some extent, the practice of whatever trade or calling they intend to adopt or have adopted, as a means of livelihood. If this view be accepted, then there is practically no limit to the activities that properly may be included in any scheme of technical education. It will embrace all grades and types of workers engaged in Trade, Industry and Commerce. Within the last thirty years practically every State in the world with any pretensions to modern civilisation has instituted and controlled a system of technical education. It is quite arguable that this is not the duty of the State but of Industry, and, as a matter of fact, many industries do shoulder this responsibility, and do it well, but in the main such training is confined to the workshop and factory, and is severely practical and narrow.
Read January 31, 1929
Keywords: Vocational education; Continuation schools; 314.15